Hereditary antithrombin deficiency in pregnancy - severe thrombophilic disorder as a danger for mother and foetus - Čápová, Irena; Salaj, Peter; Hrachovinová, Ingrid (Ceska gynekologie, 2021)
SETTING: In the article, we remember the role of antithrombin (AT) in hemostasis, escalation of AT-potential with heparin and difficulties with monitoring the effectiveness of LMWH therapy (low molecular weight heparin) in patients with AT deficiency. We pay most of our attention to hereditary AT deficiency and its thromboembolic risk in pregnancy. METHODS: In the introduction, the principle of AT function, its two main domains and the regulation of synthesis are cleared. We describe the causal mutations of hereditary AT deficiency in SERPINC1 gen and the relation to a thromboembolic risk. The general recommendations for patients with hereditary AT deficiency and pregnant women are mentioned. As the risk of thromboembolic disease is escalated in pregnancy, the LMWH should always be considered. There has been frequently observed that patients with AT deficiency do not elevate anti-Xa-levels when standard prophylactic LMWH doses are used. This fact well illustrates that heparin without AT may not inhibit the active coagulant factors efficiently enough. Therefore, if a high thromboembolic risk in the patient’s anamnesis is present, the LMWH dosing should be escalated. In individual cases, concomitant administration of an antithrombin concentrate to the heparin treatment is recommended at the time of delivery or in the case of deep venous thrombosis. In this article, three cases of unusual pregnancy in patients with different types of AT deficiency are reported. The case reports are summarized from the Department of Hematology at Hospital Kolín, the Centre of Hemostasis and Thrombosis at Institute of Hematology and Blood Transfusion in Prague and from cooperating obstetrical departments in the Czech Republic. RESULTS: We demonstrated the threat of hereditary AT deficiency in three case reports. In one case, the estimated risk of thromboembolism – type I of AT-deficiency (quantitative) – was in a good correlation with real peripartal complications. In the next two cases with different types of AT deficiency, we showed surprising courses of complicated pregnancies. CONCLUSION: As it has been shown, it is not safe to estimate the risk of thromboembolism on the base of causal mutation for AT deficiency. For present clinical practice, we should still remember AT deficiency as a potentially very dangerous thromboembolic disorder for mother and fetus; thus, excellent cooperation of an obstetrician and a hematologist is necessary.
Keywords: consumptive coagulopathy; antithrombin deficiency; Pregnancy; Humans; antithrombin; Female; antithrombotic prophylaxis; aPTT; anti-Xa; gen SERPINC1; lidé; Fetus; plod; Heparin; Heparin, Low-Molecular-Weight; ženské pohlaví; disseminated intravascular coagulopathy; Thromboembolism; nedostatek antitrombinu III; těhotenství; Czech Republic; thrombembolic disease; heparin nízkomolekulární; Česká republika; matky; Mothers; Antithrombin III Deficiency